20184538_BUSI4167_Identifying User Profile(s) for an Effective Internet Based Exercise Programme Aimed at Treating Osteoarthritis using fuzzy-set Qualitative Comparative Analysis - Vu, Thi Ngoc Linh (2020)
Recent studies raise much attention on customer’s role in value co-creation process especially in healthcare service sector. There is a consensus from previous literatures that customers actively engage in the service delivery process to receive “value-in-use” from service providers rather than seeing them as a passive value recipient. In healthcare context, knee Osteoarthritis (OA) is a common chronic disease among elders and the effective treatment for patients with this is not yet discovered. Recently, the iBEAT-OA (Internet-Based Exercise programme Aimed at Treating knee Osteoarthritis), a web-based exercise regime in home setting, is developed to treat knee OA in more efficient and effective way. This research uses COM-B model and TDF framework as a guideline to analyse factors leading to desired outcome, thus identifying the users’ profiles for the effectiveness of the App. Fuzzy-set Qualitative Comparative Analysis (fsQCA) is employed to investigate this social phenomenon especially with an input from qualitative data. In details, fsQCA allows researcher to address the causal complexity in terms of interactions among factors affecting the exercise behaviours and its desired outcome. Data including seventeen old users of the App is gathered by a team of Professor Heidi Winklhofer and given to the researcher to code, calibrate and analyse. The findings indicate that there are two solutions for the outcome to occur. Two necessary conditions are found, which are Behavioural regulation, and Beliefs about capabilities and outcome. Besides these conditions, the outcome is reachable by either the high encouragement from Facilitators from the App, or the combination of high Physical capability and high satisfaction with past treatment for knee OA. The study for patients’ characteristics reflecting who might get the benefits from the App is needed. This research contributes to healthcare service research by introducing a new approach. Rather than putting a lot of efforts on addressing every antecedent of behaviour, they should acknowledge that the different combinations of some factors can reach to the same outcome of interest.